Laws of the Personal Speech Experience Organization - Orap, Maryna (East European Journal of Psycholinguistics, 2014)
The article investigates the personality’s speech experience. Theoretical conceptual model of the speech experience considering it as structural and functional system of personality, the essence of which is the process and product of processing and organizing the results of speech development of the world by means of speech ability, speech capability, speech competency and activity through speech competence, language view of the world and speech culture. Thus, internal and external structures are found in the speech experience. Their interaction allows the personality’s speech exploration of the world. Empirical studies of structural and functional characteristics of speech experience carried out through empirical referents diagnosis the internal structure and factor analysis in order to highlight the latent variables that contribute to the functioning of the external structure. The results of the empirical study show that the organization of the internal structure of speech experience carried on the principle of differentiation. The external structure in the dynamics of its development shows the tendence to integration – the union of previously separate elements into one organized structure and bring it to the optimum number of items. Thus, the organization of speech experience going in the unity of differentiation and integration as the main processes of functioning the system. References Vinogray, Ye. (1989). Obshhaja teorija organizacii i sistemno-organizacionnyj podhod. [General Theory of the Organization and System-Organizational Approach]. Tomsk: Izd-vo Tomskogo Universiteta. Vygotsky, L. (1984). Voprosy detskoj psihologii [Issues of Child Psychology]. Vol. 4. Moscow: Pedagogika. Zalevskaya, A. A. (2000). Vvedenie v Psikholingvistiku [Introduction to Psycholinguistics]. Moscow: Russian State Humanitarian University. Laktionov, A. N. (2010). Koordinaty individual’nogo opyta [Coordinates of Individual Experience]. Kharkiv. Leontyev, A. A. (2003). Osnovy Psikholingvistiku [Foundations of Psycholinguistics]. Moscow: Smysl. Lomov, B. F. (1999). Nekotorye principy sistemnogo podhoda. Metodologicheskie osnovy sistemnogo podhoda v psihologii [Some principles of the systems approach. Methodological foundations of the system approach in psychology]. I. V. Gerasimova, Ed. Vladivostok: DVGMA. Setrov, M. I. (1972). Osnovy Funkcional’noy Teorii Organizacii [Fundamentals of the Theory of Functional Organization]. Leningrad: Nauka. Frumkina, R. M. (2001). Psikholingvistika [Psycholinguistics]. Moscow: Аcademy Chuprikova, N. I. (1997). Psihologija Umstvennogo Razvitija: Printsip differenciacii [Psychology of Mental Development: The Principle of Differentiation]. Moscow: Stoletiye.